2014
DOI: 10.1093/occmed/kqu038
|View full text |Cite
|
Sign up to set email alerts
|

The HSE Management Standards Indicator Tool: concurrent and construct validity

Abstract: Our findings consolidated the HSE-MS IT validity and showed the specific sensitivity of its scales to assess different aspects of work-related distress, including self-perception of stress at work. These results can have practical implications for the occupational well-being of employees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 20 publications
1
29
2
2
Order By: Relevance
“…The general aim of this study is therefore to better understand the relationship existing between multiple dimensions of psychosocial work stressors and male sexual function. It used the Management Standards approach of the U.K. Health and Safety Executive, which is one of the most advanced methods for the screening of work-related stress ( Edwards, Webster, Van Laar, & Easton, 2008 ; Marcatto, Colautti, Larese Filon, Luis, & Ferrante, 2014 ). The approach assesses the following seven psychosocial risks, which have the potential to lead to stress-related negative outcomes: demands, control, supervisor and peer support, relationships, change, and role.…”
mentioning
confidence: 99%
“…The general aim of this study is therefore to better understand the relationship existing between multiple dimensions of psychosocial work stressors and male sexual function. It used the Management Standards approach of the U.K. Health and Safety Executive, which is one of the most advanced methods for the screening of work-related stress ( Edwards, Webster, Van Laar, & Easton, 2008 ; Marcatto, Colautti, Larese Filon, Luis, & Ferrante, 2014 ). The approach assesses the following seven psychosocial risks, which have the potential to lead to stress-related negative outcomes: demands, control, supervisor and peer support, relationships, change, and role.…”
mentioning
confidence: 99%
“…* statistically significant (p<0.05) @ C I C E d i z i o n i I n t e r n a z i o n a l i confirmed the factorial structure and showed significant associations with other indicators linked to workrelated stress such as anxiety, depression, job satisfaction and frequency of sick leave (19,20). On the base of the results of these studies, the HSE questionnaire is considered a valid and reliable tool for the assessment of work-related stress.…”
Section: Perceived Stress and Hepatic Parametersmentioning
confidence: 71%
“…), and in the in-depth evaluation of the subjective perception of the workers of the stress related factors. The psychometric properties of this questionnaire were analyzed in many studies (19,20), which confirmed the factorial structure and showed the presence of significant associations with other indicators related to job stress such as anxiety, depression, work, satisfaction with the work and the frequency of sick leave. From the results of this research, the HSE questionnaire is considered one of the most valid and reliable instrument for the assessment of work-related stress.…”
Section: Introductionmentioning
confidence: 69%
“… To help employers, to measure the key problems inside their organization and to compare their performance with national standards, a self-report survey instrument has been developed by incorporating relevant components from Health and Safety Executive (HSE) indicator tool. Thirty five items are included in HSE Indicator Tool within the seven hazard categories (Marcatto, Colautti, Larese, Luis, & Ferrante, 2014).…”
Section: Description Of Variablesmentioning
confidence: 99%